(untitled) (Jurnal Destinasi Pariwisata, 2026)
Gili Ketapang Tourism Village, located in Sumberasih District, Probolinggo Regency, has significant potential for marine tourism development, particularly snorkeling activities supported by coral reef ecosystems and coastal attractions. However, tourism management in the area has not been optimally integrated and community participation remains uneven across different stages of development. This study aims to formulate development directions for Gili Ketapang Tourism Village based on community participation. The research employs a mixed-method approach, combining the Delphi method and a SWOT analysis strengthened by IFAS and EFAS matrices. The Delphi analysis identified 15 out of 17 tourism component indicators agreed upon by the stakeholders. Community participation is at a moderate level (48.23%), with stronger involvement in implementation and economic benefits. The SWOT analysis places Gili Ketapang Tourism Village in Quadrant I, indicating a favorable condition characterized by strong internal potential and external opportunities. Based on this, four Strength-Opportunity (S-O) strategies were formulated, including developing an integrated marine tourism package based on superior natural attractions supported by artificial tourism to capture the increasing interest of tourists, utilizing the status as a tourism village and marine conservation area to strengthen the image of sustainable marine tourism destinations thru social media-based promotion, increasing the active role of the community and management institutions (Pokdarwis and BUMDes) in managing and marketing tourism products to maximize economic opportunities from tourism, and developing and optimizing adequate tourism support facilities to sustain one-day trip visits. These strategies are expected to support the development of sustainable tourism while increasing community involvement in the management of Gili Ketapang Tourism Village.